Teaching Narrative Text In Improving Writing Skill In Second Semester of STKIP Kusuma Negara Jakarta - Dini Fitriani (Akademika: Jurnal Keagamaan dan Pendidikan, 2018)
The final project is about the teaching narrative texts in improving writing skill in second semester of STKIP Kusuma Negara Jakarta. Teaching writing is not an easy task. It requires a lot of creativity from a professional lecturer. The object of the study is to find out the students’ achievement in writing narrative texts. It is expected that the research would be useful for the lecturers and students in language teaching and learning process. The subject of the study is the second semester students of STKIP Kusuma Negara Jakarta in the academic year of 2017/2018. There were 40 students. The writer took all of them as the subject of the study. The technique used for collecting data is pre-test and post-test and interview. First, the writer gave a pre-test. It was conducted at the beginning of the research. Second, the second activity was held. It was continued with the third activity, the fourth activity, the fifth activity, the sixth activity and post-test was conducted. At last the lecturer made interview with the students about the difficulties in writing. The result of the study was that the students’ progress during teaching and learning activity by using narrative texts to improve writing skill was good. The students’ achievement in writing was improved, it was supported by the significance result of the pre-test was 62.09%; writing the first draft on the first cycle was 65.52%; writing the second draft 71.53%; writing the final copy was 74.38%; writing the first draft on the second cycle was 72%; writing the second draft was 75.42% and writing the final copy was 79.71%. Therefore, lecturers should always try to create an interesting text for their teaching. Based on the result, lecturers can apply narrative text to improve the students’ writing skill.___________________Keywords: Teaching Narrative, Writing Skill, Students of STKIP Kusuma Negara Jakarta